Biochemical Characterization of Seed Oil of Tunisian Sunflower (Helianthus annuus L.) Accessions with Special Reference to Its Fatty Acid Composition and Oil Content - Taoufik Hosni; Zouhaier Abbes; Leila Abaza; Sana Medimagh; Hamadi Ben Salah; Mohamed Kharrat (Journal of Food Quality)
Sunflower (Helianthus annuus) is a major oilseed crop, cultivated throughout the world, and the nutritional quality of its edible oil ranks among the best vegetable oils in agricultural product. In Tunisia, there is a lack of study on biochemical characterization of sunflower germplasm oil. The present study was conducted to analyze oil content and fatty acid composition of 22 local and introduced sunflower accessions. Results revealed significant variation among studied accessions for all measured biochemical traits. The average oil content of the H. annuus accessions was 53.2%, ranging from 35.33% to 59.67%. The results of this study also indicated that unsaturated acids, particularly oleic acid and linoleic acid, were the most abundant fatty acids in oils. Fatty acid compositions of sunflower oils showed diversity depending on the accession. The first two components of the principal component analysis (PCA) contributed 45.7% of the total variability. Cluster analysis based on PCA separated the accessions into four clear groups, which were not grouped according to their geographical origin. Moreover, the classification of the evaluated sunflower accessions using clustering by Euclidean distance revealed four main groups. Linoleic acid had significant and negative correlations with some saturated acids (palmitic, stearic, and arachidic acids). These data can be useful for selecting sunflower accessions and the development of varieties with improved oil quality.